Wives, concubines, or slaves? Peter Damian and clerics' women. Issue 2 (30th March 2022) - Griffiths, Fiona
Abstract : From the mid‐eleventh century, the reformed papacy launched a campaign against clerical marriage that, within a hundred years or so, would largely succeed in establishing the priesthood as a celibate (if not always chaste) caste. According to the reforming monk Peter Damian, women who associated with priests formed a particular target of papal discipline: Peter reports that Pope Leo IX ruled in 1049 that such women should be made slaves of the Roman church. This paper revisits sources concerning the reported enslavement of clerics' women, arguing that it was Peter (and not the pope) who promoted enslavement and, moreover, that Peter's ideas were never broadly adopted .